2014
DOI: 10.2174/0929867321666140716100449
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Nanosized Materials and the Brain

Abstract: The current rapid development of nanotechnologies and engineered nanomaterials (ENM) will impact the society in a major fashion during the coming decades. This development also causes substantial safety concerns. Among the many promising applications of ENM, products that can be used for diagnosis and treatment of diseases, including conditions that affect the nervous system, are under development. ENM can pass the blood brain barrier (BBB) and accumulate within the brain. It seems that the nano-form rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 86 publications
(91 reference statements)
0
23
0
Order By: Relevance
“…Reports have shown that engineered nanomaterials can enter the brain and cause tissue damage (Simkó andMattsson 2014, Lima, Guimarães et al 2019), although data about nanoparticles toxicity remain limited. Chitosan nanoparticles have already been shown to cause zebrafish embryos death and malformation (Hu, Qi et al 2011) and more recently, chitosan-coated zein nanoparticles were shown to enhance anxiety and depression in rats exposed (Lima, Guimarães et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown that engineered nanomaterials can enter the brain and cause tissue damage (Simkó andMattsson 2014, Lima, Guimarães et al 2019), although data about nanoparticles toxicity remain limited. Chitosan nanoparticles have already been shown to cause zebrafish embryos death and malformation (Hu, Qi et al 2011) and more recently, chitosan-coated zein nanoparticles were shown to enhance anxiety and depression in rats exposed (Lima, Guimarães et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed obvious toxicity of AgNPs of embryos' brain because these nanoparticles can be absorbed, and then accumulated in the brain regions by passing through the (BBB) especially in early development of embryo when the barrier is not full formed, this may be cause of some histological changes which occur in the development of early cerebellum of the embryos mainly in the mothers who receive the AgNPs during pregnancy, finally leading to dysfunctions of (CNS). Recent studies revealed that engineering nanoparticles can pass the blood brain barrier (BBB) and accumulate within the brain [10] [14]. The BBB is a well protective structure, which is mainly composed of endothelial cells, astrocytes, and pericytes [15].…”
Section: Discussionmentioning
confidence: 99%
“…Cages were cleaned and sterilized in different times with 70% ethanol. After mating, the gestational day zero was defined as the day when spermatozoa were observed in the smear taken from females'vagina, then females were transferred to separate cages without males and stayed there until the appropriate days to isolate the embryos [10].Then, the females were divided in to three groups, (G1) received (2mg/kg/ B.wt AgNPs) (G2) received 20mg/kg/B.wt AgNPs and (G3); treated as a control group and was given D.W only. The…”
mentioning
confidence: 99%
“…The last few years have seen the publication of very useful reviews on the use of nanoparticles for diagnostic and therapeutic purposes in the CNS [3][4][5].…”
mentioning
confidence: 99%